2008
DOI: 10.1039/b805754k
|View full text |Cite
|
Sign up to set email alerts
|

Lipid layers on polyelectrolyte multilayer supports

Abstract: The mechanism of formation of supported lipid layers from phosphatidylcholine and phosphatidylserine vesicles in solution on polyelectrolyte multilayers was studied by a variety of experimental techniques. The interaction of zwitterionic and acidic lipid vesicles, as well as their mixtures, with polyelectrolyte supports was followed in real time by micro-gravimetry. The fabricated lipid-polyelectrolyte composite structures on top of multilayer coated colloidal particles were characterized by flow cytometry and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
97
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(108 citation statements)
references
References 65 publications
9
97
1
1
Order By: Relevance
“…This could offer substantial advantages in bioreactor construction, particularly for biomimetic systems where complex mixtures of macromolecules in nearly identical interior microenvironments are desirable across a population of bioreactors, and where the impermeability of giant vesicle lipid bilayer membranes to even relatively small solutes restricts the types of reactions that can be performed. The observation that aqueous/aqueous interfaces can template assembly of liposome submonolayers also suggests the intriguing possibility that such structures could ultimately be converted into contiguous lipid bilayer membranes by rupture and in-plane restructuring of the assembled liposomes, similar to the formation of supported lipid bilayers on bare and polymercoated solid surfaces [51][52][53] . Such a process would be of interest for generating uniform populations of 'pre-loaded' artificial cells and could serve as a mechanism for cellularization of primitive Pickering-style protocells.…”
Section: Discussionmentioning
confidence: 99%
“…This could offer substantial advantages in bioreactor construction, particularly for biomimetic systems where complex mixtures of macromolecules in nearly identical interior microenvironments are desirable across a population of bioreactors, and where the impermeability of giant vesicle lipid bilayer membranes to even relatively small solutes restricts the types of reactions that can be performed. The observation that aqueous/aqueous interfaces can template assembly of liposome submonolayers also suggests the intriguing possibility that such structures could ultimately be converted into contiguous lipid bilayer membranes by rupture and in-plane restructuring of the assembled liposomes, similar to the formation of supported lipid bilayers on bare and polymercoated solid surfaces [51][52][53] . Such a process would be of interest for generating uniform populations of 'pre-loaded' artificial cells and could serve as a mechanism for cellularization of primitive Pickering-style protocells.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,14 In this regard, it has already been shown that LbL particles are sufficiently taken up by living cells, which subsequently express proteins that are encoded on the plasmid encapsulated into the LbL particles. 12 Typically, the particle uptake occurs in a non-receptor-mediated endocytotic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…8 Spherical supported membranes are formed not only on silica beads 9 but also on layer-by-layer (LbL) polymer coated surfaces. [10][11][12] Such LbL particles and capsules are generated by adsorption of anionic and cationic polyelectrolytes on spherical support in an alternating arrangement. 13 LbL particles can be easily functionalized, are highly stable, offer a large size range (from 100 nm to 15 mm), are monodisperse, possess a tuneable permeability, and are biodegradable.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations